PENGARUH BRAND AMBASSADOR DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PENGGUNAAN APLIKASI ALLO BANK PADA MASYARAKAT UMUM - Sekar Nirwana Ros Sinta Aji; Raisya Putri Syafna Azzahra; Yossy Marsyatrinisa; Asep Maulana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to answer the researcher's assumptions by examining the influence of brand ambassadors, consumer trust, and the decision to use Allo Bank services among the general public. The research method used is descriptive quantitative with data collection through a questionnaire on Google Forms. The study was conducted with 100 respondents. The analysis method used multiple linear regression with the SPSS application. The results of the study indicate that brand ambassadors have a significant influence on the decision to use Allo Bank services. Based on the results of the study, it can be concluded that good brand ambassadors from a brand and influencers promoting Allo Bank can increase influence, trust, and the decision to use services. Therefore, companies need to pay attention to these factors in an effort to increase customer usage decisions.